Discussing the Concept of “Hierarchy” in Urban Planning Studies - Berkmen, Naime Hülya; Biçer, Merve (İstanbul Üniversitesi, 2024)
While preparing analysis, synthesis, and planning approaches in City and Regional Planning studies, the concept of "hierarchy" is important at all stages, regardless of the location and size of the planned settlement. In these studies, the role of settlement within its country, region, sub-region, identity, potentials, problems, and dynamics within production-consumption relations are explained with the concept of "hierarchy". Various components of settlements through this concept; Transportation, centre size, green and open areas, and population and building density distributions, are important in terms of determining priorities qualitatively and quantitatively. There are criteria that determine the degree/content of “hierarchy” in discussions of every function, sector, and size. Although there are criteria that determine inter-scale, inter-plan, inter-sectoral, and inter-functional staging in urban planning studies in Turkey, including the urban design scale from upper-scale plans, the inconsistencies between accepted criteria both in public institutions and organisations related to urban planning, in academic studies, and in the legal system, the criteria are not updated according to changing conditions, and there is a lack of comparative database; It makes it difficult to make healthy analysis, analysis, and make decisions for the future. This study discusses the “settlement hierarchy” criteria, which differ and need to be updated, within the scope of administrative borders, jurisdictional borders, and criteria determining borders.
Keywords: Architecture (Other); Mimarlık (Diğer)